Temporal Changes in Serum S100B Levels From Prehospital to Early In-Hospital Sampling in Patients Suffering Traumatic Brain Injury - Seidenfaden, Sophie-Charlott; Kjerulff, Julie Linding; Juul, Niels; Kirkegaard, Hans; Fogh Møller, Mette; Bloch Münster, Anna-Marie; Thingemann Bøtker, Morten (Frontiers in Neurology, 2022)
Background: The biomarker S100B is used for rule-out of intracranial lesions in mild traumatic brain injury (TBI) patients and suggested for prehospital use in Europe. Early kinetics of S100B are not exhaustively investigated in human TBI. This post-hoc descriptive study of data from the PreTBI studies aimed to characterize the early temporal changes of S100B using two sample timepoints. Materials and methods: Two consecutive blood samples were taken prehospital and inhospital after injury and assayed for S100B. Endpoint adjudication of the outcome intracranial lesion was done by evaluation of electronic medical patient journals. Data was analyzed using descriptive statistics, scatterplots and temporal changes estimated by LOWESS regression line. Results: A total of 592 adult TBI patients were included; 566 with GCS 14-15, 20 with GCS 9-13 and 6 with GCS 3-8. Intracranial lesions were diagnosed in 44/566 (7.4%) of patients. In 90% of patients, S100B concentrations decreased from prehospital to inhospital sampling. Mean decrease was -0.34 ug/L. S100B concentrations seem to decline already within 60 min. Patients sampled very close to trauma and patients suffering intracranial lesions may express a slight incline before this decline. Temporal changes of S100B did not differ in patients > 65 years of age, in antiplatelet/-coagulant treatment, alcohol intoxicated nor suffering extra-cranial injuries. Conclusion: S100B concentrations may peak earlier than expected from previous studies of temporal changes in human TBI. Patterns of S100B stands robust to parameters stated as limiting factors to the use for early rule-out of intracranial lesions in the current guidelines. Further studies are needed to investigate the ultra-early temporal profiles of other novel TBI biomarkers in order to asses prehospital applicability and optimal diagnostic performance in TBI.